Nilai-Nilai Pendidikan Islam pada Tradisi Sakura dan Implikasinya dalam Menumbuhkan Sikap Humanis Pada Masyarakat Lampung Pesisir Kabupaten Lampung Barat - Simona, Rian; Syafe'i, Imam; Safari, Safari (Attractive : Innovative Education Journal, 2024)
Lampung society is known as a society that adheres to tradition in understanding the reality of its social life, including the cherry blossom tradition. The cherry blossom tradition is a tradition that originates from West Lampung. The sakura tradition is a masked party held every Eid al-Fitr holiday with the main aim of keeping in touch. This research aims to describe and analyze the values of Islamic education in the cherry blossom tradition and their implications in fostering a humanist attitude in the people of Coastal Lampung, West Lampung Regency. The research used in this study is qualitative research with the type of field research, while the method used is ethnography or culture-based research. The study was carried out in West Lampung. Data collection was carried out by means of observation, document collection and interviews. Data sources include interviews with traditional leaders, community leaders and youth leaders. This study shows the results that there are values of Islamic education in the sakura tradition, namely: 1) Praying together and saying takbir sentences which have the value of thanking Allah SWT for the blessings of faith. Islam and obedience, 2) Buhippun or deliberation, mutual cooperation and giving alms which have the values of mutual respect, respect and unity, 3) Njalang or halal bihalal which have the values of friendship and good manners. The implications of the values of Islamic education in the cherry blossom tradition in cultivating a humanist attitude in the people of Lampung Coastal West Lampung Regency, this is reflected in attitudes 1) Mutual respect, 2) Polite attitudes, 3) Mutual assistance attitudes, 4) Kinship attitudes and tolerance attitude. Keywords: Islamic Education Value, Tradition, Humanism